MENUMBUHKAN BUDAYA LITERASI DENGAN MENGGUNAKAN “PROGRAM KATA” DI SMA MUHAMMADIYAH TOBOALI KAB. BANGKA SELATAN - Supiandi, Supiandi (STUDIA: JURNAL HASIL PENELITIAN MAHASISWA, 2016)
The lack of reading culture in indonesiahas big correlation with the weakness of writing culture. Because of that reason,we have to do something that can increase and improve the reading and writing culture in every part of society, especially at the education background. The goverment through the Minister of education has issued about the roles due to improving of attitude includes the School Literation Movement (SGL) that asks the students to read the fiction books about 10-15 minutes before the lessons begin. The aim of this movement is to improve the reading and writing (literation) to all the people at schools, includes the headmasters, students and teachers. this process is expected to increase the ability of reading understanding analitically, critically and refletively. The problems of the application from thisSGL programme are : 1. The students' interest in reading and writing activitiesare very low. 2. The lack of non-learning books at the school library. 3. The librariandoesn't support the students needs. 4. The apprecation of the students related to the literationis is very low.5. The teachers as the model figure don't show the good way in literation. The bestsolutions to help SGL programworking is the words programme that relates to the increase the culture of reading and writing activities (literation) at schools. This programehave three programmes implementation, they are :1. Elibrary,2. The words mentoring, 3. The words choices.